Fibrinolytic Activity in Chinese Patients with Diabetes or Hyperlipidemia in Comparison with Healthy Controls - Ho, Chao Hung; Jap, Tjin Shing (Thrombosis and Haemostasis, 1991)
Plasma tissue-type plasminogen activator (tPA), plasminogen activator inhibitor (PAI) and euglobulin lysis time (ELT) were determined before and after the venous occlusion test (VOT) in 3 groups of patients with mean age about 60 years: 29 diabetic patients (D group), 8 hyperlipidemic patients (H group) and 19 healthy controls (C group). In the D and H groups, the mean of morning tPA was significantly higher than that of the C grogp, but the means of PAI were not significantly different among the 3 groups. ELI was significantly shortened and tPA was markedly increased after the VOT in all 3 groups whereas PAI had not significantly changed. In conclusion, high tPA activity and good fibrinolytic response without significant change of PAI .activity were found in the diabetic and hyperlipidemic patients, and no definite impairment of the fibrinolytic activity could be found in the Chinese patients with diabetes and hyperlipidemia. This might be one of the reasons why the Chinese has low incidence of thromboembolic diseases.